The impact of general and central obesity for all-cause hospitalization among Iranian adults: a 20 year follow-up-results from the TLGS cohort - Azra Ramezankhani; Fereidoun Azizi; Mitra Hasheminia; Farzad Hadaegh (BMC, 2023)
Abstract Background Few studies have examined the effect of obesity indices on total number of hospitalizations. We examined the associations between body mass index (BMI) and waist circumference (WC) and rate of all-cause hospitalizations among Iranian adult participated in the Tehran Lipid and Glucose Study cohort. Methods This study included 8202 individuals (3727 men) aged ≥ 30 years, who were followed for a median of 18 years. Participants were categorized into three groups according to their baseline BMI: normal weight, overweight and obese. In addition, they were classified according to WC in two categories: normal WC and high WC. Negative Binomial regression model was used to estimate the incidence rate ratios (IRRs) and 95% confidence interval (95% CI) of all-cause hospitalizations in relation to obesity indices. Results The overall crude rate of all-cause hospitalizations were 77.6 (95% CI, 73.9-81.2) and 76.9 (73.4-80.3) per 1000 person-year in men and women, respectively. The covariate adjusted rate of all-cause hospitalizations was 27% higher in obese men than normal weight men (IRR (95% CI): 1.27 (1.11-1.42)). Among women, overweight and obese individuals had 17% (1.17 (1.03-1.31)) and 40% (1.40 (1.23-1.56)) higher rate of hospitalization compared to normal weight women. Having high WC was associated with 18% (1.18 (1.08-1.29)) and 30% (1.30 (1.18-1.41)) higher rate of all-cause hospitalization in men and women, respectively. Conclusions Obesity and high WC were associated with increased hospitalization rates during long-term follow-up. Our findings suggests that successful obesity prevention programs may decrease the number of hospitalizations, particularly, in women.